2007
DOI: 10.12930/0271-9517-27.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Charting the Verbiage of Institutional Vision: Implications for Academic Advising

Abstract: Whether and to what extent a college or university vision is embraced, transformed into action, and dispersed to the campus community by academic advisors is largely dependent on the rhetoric of the vision statement. Through a content analysis of a nation-wide sample of vision and mission statements from NACADA-membership institutions, we isolated key linguistic components that constitute a well-conceived, effective, and easily diffused institutional vision. The prevalence of these components and the types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Abelman et al (2007) also found that mission statements tend to be less clear, less compelling, and have less observabilitythat is, the desired outcomes are less practical and less pragmatic-than vision statements. Conversely, mission statements tend to be longer, more complex, and have greater relative advantage-that is, the language reflects more movement, change, and the implementation of ideas-than vision statements.…”
Section: The Verbiage Of Institutional Visionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abelman et al (2007) also found that mission statements tend to be less clear, less compelling, and have less observabilitythat is, the desired outcomes are less practical and less pragmatic-than vision statements. Conversely, mission statements tend to be longer, more complex, and have greater relative advantage-that is, the language reflects more movement, change, and the implementation of ideas-than vision statements.…”
Section: The Verbiage Of Institutional Visionmentioning
confidence: 99%
“…This, in turn, may render the vision statement of increased significance to an institution and warrant a wider or more purposeful distribution to its stakeholders. Abelman et al (2007) found that tribal, military, and religious institutions tended to be more "vision-driven" in their operations than other types of colleges and universities. A significant proportion of private HBCUs are affiliated with religious institutions (Brown & Freeman, 2004;Cole & Wortham, 2000).…”
Section: Research Question 1: What Constitutes Institutional Vision Imentioning
confidence: 99%
See 1 more Smart Citation
“…According to Morphew and Hartley (2006), institutional vision statements now serve as icons that communicate with stakeholders who have specifi c expectations of colleges and universities that "have important legitimizing roles, both normatively and politically" (p. 468). Abelman, Dalessandro, Snyder-Suhy, Janstova, and Pettey (2007) found that vision and mission statements at secular academic institutions appear to serve different, albeit highly complementary, functions. Although mission statements are prevalent across most academic institutions, only one-third of all 4-year colleges and universities possess actual vision statements.…”
Section: The Verbiage Of Institutional Visionmentioning
confidence: 99%
“…According to Morphew and Hartley (2006), these statements now serve as icons that communicate with stakeholders who have specific expectations of colleges and universities and that "have important legitimizing roles, both normatively and politically" (p. 468). Abelman, Dalessandro, Janstova, Snyder-Suhy, and Pettey (2007) found that vision and mission statements at academic institutions appear to serve different, albeit highly complementary functions. Although mission statements are prevalent across most academic institutions, only one third of all 4-year colleges and universities possess actual vision statements.…”
Section: The Verbiage Of Institutional Visionmentioning
confidence: 99%